Validation by piv of the numerical study of flow in the two-dimensional turning diffuser - Nordin, N. (Asian Research Publishing Network, 2016)
The primary objective of this study is to validate the numerical method applied in the analysis of two-dimensional turning diffuser performance. A sharp 90o two-dimensional turning diffuser of area ratio, AR = 2.16 operated at inflow Reynolds numbers, Rein = 5.786 x 104 - 1.775 x 105 was considered. The applicability of standard (ske), renormalization group (rngke) and realizable (rke) k-s turbulence models adopted various near wall treatments namely standard wall functions, non-equilibrium walls functions and enhanced wall treatment to simulate the actual cases was assessed. The ske adopted enhanced wall treatment of y+ = 1.1 - 1.8 appears as the best validated model, producing minimal deviation with comparable flow structures to the experimental cases (using particle image velocimetry). Â©2006-2016 Asian Research Publishing Network (ARPN).